Isolated tenosynovitis as a sole manifestation: The great mimicker still continues to surprise Us - Abhishek De; Trupti V Surana; Saugato Biswas; Abu Hena Hasanoor Reja; Gobinda Chatterjee (Wolters Kluwer Medknow Publications, 2015)
A middle aged male presented with non-tender cystic swelling over left distal forearm since 1 year. No other cutaneous abnormality could be found except mild paresthesia of the overlying skin and equivocal thickening of the ipsilateral ulnar nerve. Routine investigation was within normal limits. Detailed workup of the patient including MRI of the lesion suggested the diagnosis as tenosynovitis with a soft tissue mass. Fine needle aspiration cytology from the cyst showed foamy macrophages and acid fast bacilli; while PCR of the aspirate confirmed the etiological agent as M. leprae. We, thus, report a unique case of isolated tenosynovitis as a sole manifestation of pure neural leprosy which is extremely rare in world literature.